Toxoplasma encephalitis after initiation of highly active anti-retroviral therapy (Haart) - Pereira, Ivete A.E.; Ferry, Fernando Raphael A.; Alvarenga, Regina Maria P.; Sá, Carlos Alberto M. (Brazilian Journal of Sexually Transmitted Diseases, 2008)
Since 1983, Toxoplasma encephalitis (TE) is the neurological disorder most frequently found in HIV/AIDS patients. It commonly develops as a reac tivation, and its etiological agent is the obligatory intra-cellular protozoan Toxoplasma gondii (T. gondii). The parasite seropositive rate, which varies in different parts of the world but is significantly high in most of them, is what keeps concern about TE constantly present. The first antiretrovirals favored the same class and were used in single therapies; they were incapable of promoting sufficient immunological recovery to avoid opportunistic diseases and, furthermore, the concept of either primary or secondary prophylaxis had not been established at the time. In 1996 the appearance of two new antiretroviral classes triggered a new treatment concept. The existing prophylactic procedures were associated to a Highly Active Antiretroviral Therapy (HAART), a behavior that showed its efficacy in reducing the number of cases. Toxoplasma encephalitis has recently been described with an immune reconstruction inflammatory syndrome (IRS) related to the rapid response to HAART in severely immunodepressed individuals. Reports on reactivation or relapse noted in patients with sustained immunological recovery, when it is safe to suspend prophylaxis, suggest the participation of more aggressive T. gondii strains or factors inherent to the host. It is therefore necessary to carry out more wide-ranging studies to clarify the link bet ween parasite/host and chronic/reactivated infections of cysts. Other alternatives to the treatment and prophylaxis of AIDS and TE that facilitate the adhesion of the patient to the first approach, as well as the definition of the serological status for T. gondii and the adoption of prophylactic measures related to primary infection cases, can largely contribute to reduce the number of TE cases.